Developing students’ mathematical creative thinking skill through joyful learning strategy in algebra (PRISMA, Prosiding Seminar Nasional Matematika, 2020)
Along with the rapid development of technology in the 21st century, students must have some skills that must be mastered by each student, called 4C. Creative thinking skill is the ability to solve a problem through many ways. Creative thinking skills can be implemented in many subjects in school, included in mathematics, applied in algebraic topic. This study aims to find out the development of student's mathematical creative thinking skills in algebra. Joyful learning strategy was done for this study. To get data, researchers used qualitative descriptive approach based on literature review. The data sources were selected from research paper published from 2015 until 2018 in accordance with the problems of the study. The abilities of students' creative thinking are divided into five different skill levels, from not creative until very creative, and also divided into three categories based on their prior knowledge. Students feel the interesting atmosphere in learning, relax, and attractive so as to make the student spirit and high concentration during lessons. This study concluded that creative thinking skills can be developed through joyful learning.